Exploring the Impacts of an Early Childhood Educational Intervention on Later School Selection. (December 2020) - Watts, Tyler; Ibrahim, Deanna; Khader, Alaa; Li, Chen; Gandhi, Jill; Raver, Cybele
In the current article, we examine the long-run school selection patterns of children randomly assigned to the Chicago School Readiness Project, an early childhood educational (ECE) intervention that aimed to improve the quality of Head Start classrooms serving low-income communities. Analyses suggest that adolescents who participated in the program were more likely to opt out of their assigned neighborhood school and attend schools with better indicators of academic performance. Further analyses suggested that these selection patterns began in elementary school, although elementary school quality explained only a small portion of the effect on high school selection. Results suggest that intensive ECE interventions could have lasting effects on children's patterns of selection into later educational environments.